Maintenance of roof structure in high-rise residential flat buildings / Noorashikin Kamaludin - Kamaludin, Noorashikin (2008)
The purpose of this research is to understanding about the maintenance of roof structure in high-rise residential flat buildings. The author was investigated the implementation maintenance of roof structure in four (4) number of case studies. The study will be carried out based on the high-rise residential flat buildings in Shah Alam, Selangor and Kuala Lumpur. In addition, this research is about the understanding of the roof construction, types of defect found in the roof structure and also the causes of roof failure. Method of eliciting included interview and questionnaire. Information was collected by secondary sources like handbooks and internet. Leaks on a flat or pitch roof can be caused by several items, faulty seam, clogged drain, failed caulking, or a deteriorated flashing. In some cases, water may travel several feet along rafters and through insulation before it actually drips into the building and will cause a problem to occupant especially who live in the upper floor of the buildings. So, routine roof inspection and maintenance program should be carried out to maximize the life span of the roof structures and also to ensure the safety of occupant in that building.